Photopharmacology reveals high-specificity linkage of Ca2+ entry at TRPC6 nanodomains to NFAT activation in mast cells - Krivić, Denis; Panasiuk, Olga; Pilic, Johannes; Malli, Roland; Bacsa, Bernadett; Ćurčić, Sanja; Groschner, Klaus (Frontiers in Immunology, 2025)
IntroductionPhotopharmacology has recently emerged as a strategy for high-precision modulation of immune functions. Here we explored efficiency and specificity of interventions based on light-induced TRPC6 activation in the RBL-2H3 mast cell model.ResultsExpression of TRPC6 fusion constructs in RBL-2H3 allowed for generation of temporally well-defined, cytosolic Ca2+ transients in response to photoisomerization of the TRPC6 actuator OptoBI-1. These Ca2+ signals originated exclusively from Ca2+ entry across the plasma membrane. Transient TRPC6 activation in response to UV pulses of 1s duration (3 mW/cm2) just exceeded the detection threshold for monitoring of Ca2+ signals within the TRPC6-jRGECO1a nano/microdomain. Activation of TRPC6-jRGECO1a by single, 1s UV light pulses was sufficient to trigger maximal cytosolic to nuclear translocation of NFATc1 (NFAT2) equivalent to the level generated by ionomycin (1 µM)-induced Ca2+ entry. TRPC6 photopharmacology enabled control over NFATc1 nuclear translocation devoid of any detectable degranulation responses.ConclusionWe report here the exceptionally efficient and specific modulation of mast cell activity by TRPC6 photopharmacology.